Pengembangan Tradisi Keilmuan Pondok Pesantren: Development of the Scientific Tradition in Islamic Boarding Schools - Sarwan Sarwan (Fenomena, 2014)
Islamic boarding schools are believed to be an alternative solution to current educational problems. One of the management changes is the emergence of the development of boarding school traditions that combine Islamic education—synonymous with classical books—with general education, professional systems and methods, and skill provision for students. Thus, boarding schools, which were originally focused solely on Salaf education, are now seeing the emergence of Islamic boarding schools that incorporate general subject materials and science skills. Additionally, Islamic boarding schools are also striving to provide educational institutions that meet the needs of students, equipped with managerial techniques appropriate to changing demands. This study focuses on the scientific tradition of Islamic boarding schools. Pondok pesantren diyakini sebagai alternatif solusi bagi permasalahan pendidikan saat ini. Salah satu perubahan manajemen yang terjadi adalah munculnya pengembangan tradisi pesantren yang menggabungkan pendidikan Islam—yang identik dengan kitab-kitab klasik—dengan pendidikan umum, sistem dan metode profesional, serta pembekalan keterampilan bagi santri. Dengan demikian, pesantren yang awalnya hanya berfokus pada pendidikan salaf, kini mulai bermunculan pesantren yang memasukkan materi-materi pelajaran umum dan keterampilan sains. Selain itu, pesantren juga berupaya menyediakan lembaga pendidikan yang sesuai dengan kebutuhan santri, dilengkapi dengan teknik manajerial yang sesuai dengan tuntutan perubahan. Penelitian ini berfokus pada tradisi keilmuan pondok pesantren.